Intermittent Pringle maneuver is unlikely to induce bacterial translocation to the portal vein: a study using bacterium‐specific ribosomal RNA‐targeted reverse transcription‐polymerase chain reaction. (17th March 2015) - Yamaguchi, Naoya; Yokoyama, Yukihiro; Ebata, Tomoki; Igami, Tsuyoshi; Sugawara, Gen; Asahara, Takashi; Nomoto, Koji; Nagino, Masato
Abstract Background The occurrence of bacterial translocation (BT) to the mesenteric lymph nodes following the Pringle maneuver is well established; however, the incidence of BT to the portal circulation remains unclear. Methods Portal blood of patients with suspected hilar malignancy who underwent major hepatobiliary resection with cholangiojejunostomy was sampled three times during surgery: immediately after laparotomy (PV‐1); before liver transection and after skeletonization of the hepatoduodenal ligament (PV‐2); and after completion of the liver transection (PV‐3). The samples were analyzed for microbes with a bacterium‐specific ribosomal RNA‐targeted reverse transcription‐polymerase chain reaction method. Results Fifty patients were enrolled in the study, with a mean total Pringle time of 86 min. Microbes in the portal blood were detected in 11 (22%) of the 50 patients. The occurrence of microbes was not different among the PV‐1 samples (8% = 4/50), PV‐2 samples (14% = 7/50), and PV‐3 samples (14% = 7/50) (P = 0.567). Obligate anaerobes were predominantly detected. The positivity of the PV‐3 samples showed no correlation with the total Pringle time or with the occurrence of postoperative infectious complications. The total Pringle time did not affect the surgical outcomes, including infectious complications, liver failure, or mortality. The concentrations of aspartate aminotransferase and alanine aminotransferase on postoperative day 1 significantly correlated with the total Pringle time. Conclusions The intermittent Pringle maneuver is unlikely to induce BT to the portal circulation and is safe, even in difficult, complicated hepatobiliary resections requiring long clamping times.